Carbamate Synthesis Using a Shelf‐Stable and Renewable C1 Reactant. Issue 13 (11th June 2019) - Dobi, Zoltán; Reddy, B. Narendraprasad; Renders, Evelien; Van Raemdonck, Laurent; Mensch, Carl; De Smet, Gilles; Chen, Chen; Bheeter, Charles; Sergeyev, Sergey; Herrebout, Wouter A.; Maes, Bert U. W.
Abstract: 4‐Propylcatechol carbonate is a shelf‐stable, renewable C1 reactant. It is easily prepared from renewable 4‐propylcatechol (derived from wood) and dimethyl carbonate (derived from CO2 ) using a reactive distillation system. In this work, the 4‐propylcatechol carbonate is used for the two‐step synthesis of carbamates under mild reaction conditions. In the first step, 4‐propylcatechol carbonate is treated with an alcohol at 50–80 °C in the presence of a Lewis acid catalyst, such as Zn(OAc)2 ⋅2 H2 O. With liquid alcohols, no solvent is used and with solid alcohols 2‐methyltetrahydrofuran is used as solvent. In the second step, the alkyl 2‐hydroxy‐propylphenyl carbonate intermediates obtained react with amines at room temperature in 2‐methyltetrahydrofuran, forming the target carbamates and the byproduct 4‐propylcatechol, which can be recycled into a carbonate reactant. Abstract : Shelf control : 4‐Propylcatechol carbonate is a shelf‐stable and renewable C1 reactant and can be used for the synthesis of carbamates in two consecutive steps under mild reaction conditions. It is prepared easily from renewable 4‐propylcatechol (derived from wood) and dimethyl carbonate (derived from CO2 ) by using a reactive distillation system. The byproduct 4‐propylcatechol can be recycled.